The Vela Pulsar and Its Pulsar Wind Nebula Vela-X Using 13 Yr of Fermi-LAT Observations - Alexander Lange; J. Eagle; O. Kargaltsev; Lucien Kuiper; Jeremy Hare (The Astrophysical Journal, 2025)
We present results of more than 13 yr of Fermi–Large Area Telescope (LAT) data analysis for the Vela pulsar from 60 MeV to 100 GeV and its pulsar wind nebula (PWN), Vela X, for E  > 1 GeV in the off-pulse phases. We find that the Vela X PWN can be best characterized using two extended components: a large radial Gaussian accompanied by an offset, compact radial disk, both with a similar spectral index, Γ ∼ 2.3. The common spectral properties support a common PWN origin, but a supernova remnant component is plausible for the compact radial disk. With an updated Vela X model, the phase-resolved spectral properties of the Vela pulsar are explored through a phase-resolved analysis. The phase-resolved spectral properties of the pulsar, such as the spectral energy distribution (SED) peak energy E _p , the width of the SED at its peak d _p , and the asymptotic (low-energy) spectral index Γ _0 , are presented. The best-fit spectral models for each LAT pulse peak (Peak 1 and Peak 2) are extrapolated to UV energies and compared to archival, phase-resolved spectra at UV, X-ray, soft γ- ray, and TeV energies. We also discuss the physical implications of our modeling and the data comparisons.